2021
DOI: 10.3389/fmolb.2020.627827
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA NEAT1 Promotes High Glucose-Induced Mesangial Cell Hypertrophy by Targeting miR-222-3p/CDKN1B Axis

Abstract: Glomerular hypertrophy is an early morphological alteration in diabetic nephropathy. Cyclin-Dependent Kinases have been shown to be required for high glucose (HG)-induced hypertrophy; however, the upstream regulators of CDKN1B in glomerular hypertrophy remain unclear. Herein we describe a novel pathway in which Long noncoding RNA (lncRNA) NEAT1 regulates the progression of mesangial cell hypertrophy via a competing endogenous RNA (ceRNA) mechanism. Real-time PCR was performed to detect the relative NEAT1 and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 33 publications
1
21
1
Order By: Relevance
“…G Wolf et al reported that HG promoted p27Kip1 expression in cultured mouse mesangial cells and may concubine to the process of diabetic glomerular hypertrophy [23]. Liao et al demonstrated that NEAT1 accelerated HG-induced mesangial cell hypertrophy by regulating miR-222-3p/CDKN1B axis [24]. In the current study, we found that CDKN1B was the direct target of miR-2861, as evidenced by the bioinformatics prediction, dual-luciferase-reporter gene and western blotting assay.…”
Section: Discussionsupporting
confidence: 65%
“…G Wolf et al reported that HG promoted p27Kip1 expression in cultured mouse mesangial cells and may concubine to the process of diabetic glomerular hypertrophy [23]. Liao et al demonstrated that NEAT1 accelerated HG-induced mesangial cell hypertrophy by regulating miR-222-3p/CDKN1B axis [24]. In the current study, we found that CDKN1B was the direct target of miR-2861, as evidenced by the bioinformatics prediction, dual-luciferase-reporter gene and western blotting assay.…”
Section: Discussionsupporting
confidence: 65%
“…With regard to DKD, others showed a positive and negative correlation, respectively, between elevated urinary NEAT1 and various podocyte damage markers like synaptopodin and podocalyxin or GFR [ 42 ]. HG-exposed proximal tubular cells (HK-2) or murine MCs (mMCs) exhibited an increase in NEAT1 expression in a dose- or time- dependent manner [ 31 , 43 ]. Contrarily to others, our data indicate that NEAT1 expression is not affected by HG using an osmotic control and a species model, in which NEAT1 is annotated (human or murine) [ 31 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, more and more studies have revealed that lncRNAs function as its biological role in this way. In the study we demonstrated that L13Rik acts as a ceRNA to sponge miR-2861, resulting in the de-repression of its target CDKN1B, a gene known to accelerate MC injury (Liao et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The cell-cycle arrest is a hallmark of MC hypertrophy (Shankland, 1999), and cyclin-dependent kinase inhibitor 1A (CDKN1A), a kind of cyclin-dependent kinase inhibitor, is required for glomerular hypertrophy in experimental DN (Al-Douahji et al, 1999). In addition, up-regulated CDKN1B by lncRNA-NEAT1 promotes MC hypertrophy (Liao et al, 2020). In the present study, we demonstrated that L13Rik was significantly increased in DN patients and rats, and L13Rik depletion effectively reduced HG-induced MC survival, ECM accumulation, and cell hypertrophy through sponging miR-2861 and thus de-repressing its target CDKN1B.…”
Section: Introductionmentioning
confidence: 99%